Perbedaan Kadar Hemoglobin Metode Sianmethemoglobin dengan dan Tanpa Sentrifugasi pada Sampel Leukositosis - wahdah norsiah (Medical Laboratory Technology Journal, 2015)
Examination of hemoglobin levels influenced leukocytosis sianmethemoglobin method that causes increased absorbance measurements of hemoglobin levels increased significantly and the false blood sample that has been diluted with a solution Drabkins in centrifugation at 3000 rpm for 10 minutes and then the absorbance of the supernatant was measured with a photometer at λ 546 nm. This study aimed to analyze the differences in hemoglobin level examination siamethemoglobin method with and without centrifugation at sample leukocytosis. This type of research is observational research laboratory. The study design was cross-sectional study. Samples were taken from the remaining blood samples of patients who have been examined leukositnya number more than 20,000 / uL with Hematology Analyzer (CEL-DYN Ruby) February-April 2014, and were divided into 4 groups based on criteria that group 1. leukocyte count of 20,000 / uL-29 999 / mL, group II. 30,000 / uL-39 999 / uL, the group III. 40,000 / uL-49,999 / uL, the group IV. More than 50,000 / uL. The number of samples taken were 20 samples of each group, a total sample of 80 samples. The analysis showed no significant difference in hemoglobin levels siamethemoglobin method with and without centrifugation at sample leukocytosis with a value of p = 0.000 less than 0.05 α. Leukocytosis Turbidity affects the difference in hemoglobin levels with and without centrifugation, the higher the number the greater the difference in leukocyte levels of hemoglobin, hemoglobin level examination results of the study based on the criteria of the number of leukocytes obtained by the difference in hemoglobin levels with and without centrifugation in group I. 0.22 ± 0.07 g / dL, group II 0.40 ± 0.22 g / dL, a group III. 0.44 ± 0.14 g / dL, Group IV. 0.85 ± 0.41 g / dL. The level of hemoglobin in the sample sianmethemoglobin method leukocytosis with more than 20,000 / uL need a centrifuge so that appropriate hemoglobin levels over the patient's clinical condition.